Antitubercular Drug induced Hepatitis: An Adverse Drug Reaction - Begum, Aisha; Parveen, Uzma; Sultana, Safura; Fatima, Nausheen; Fareedullah, Mohd; Z, Zareenunnisa (Indian Journal of Pharmacy Practice)
Antitubercular drugs are the first line agents for the management of tuberculosis. Drug induced hepatotoxicity is an unexceptional adverse effect mostly caused by antitubercular drugs leading to cessation of therapy. The keystone for the treatment of tuberculosis is a 6-month regimen consisting of drugs such as Isoniazid, rifampicin, pyrazinamide and ethambutol. Although Antitubercular drugs are only option for the treatment for pulmonary TB, Hepatotoxicity is one of the most detrimental adverse events leading to interruption of treatment thereby causing drug resistance. In this case the patient was recently diagnosed with pulmonary tuberculosis one month ago, consequently developed hepatotoxicity due to use of anti-tuberculosis drugs. Naranjo Adverse Drug Reaction Probability Scale was used to assess the adverse Drug effect and the score was found to be probable thereby indicating that Anti TB drugs cause hepatitis.
Keywords: Anti-tuberculosis drugs; Hepatotoxicity; Pulmonary TB; Adverse effect; Drug resistance